1975
DOI: 10.1113/jphysiol.1975.sp010899
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet cells: effects of monosaccharides, glycolytic intermediates and metabolic inhibitors on membrane potential and electrical activity.

Abstract: SUMMARY1. The effects of monosaccharides, glycolytic intermediates, metabolic inhibitors and anoxia, have been studied on the membrane electrical activity of mouse pancreatic islet cells in vitro using a single intracellular micro-electrode for both voltage recording and current injection. 4. Electrical activity induced by D-glucose 28 mm, was progressively inhibited by phloridzin, 10 mm, if the cells were exposed to D-glucose and inhibitor simultaneously, and abolished on pretreatment with inhibitor for 30-60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

1978
1978
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 34 publications
4
46
0
1
Order By: Relevance
“…Since the hyperpolarization stabilized at an estimated value close to EK it can be suggested that KATP channels were activated by removal of glucose. To our knowledge this is the first report demonstrating hyperpolarization by glucose deprivation in a cell type other than the pancreatic â_cells (Dean, Matthews & Sakamoto, 1975;Ashcroft, Ashcroft & Harrison, 1988) and the glucose-sensitive neurons (Ashford, Boden & Treherne, 1990). Since hyperpolarization induced by glucose removal was observed in pyruvate-containing as well as pyruvate-free solutions, the ATP generated by pyruvate oxidation in the mitochondria apparently did not affect the activity of KATP channels.…”
Section: Hyperpolarization Induced By Glucose Deprivationmentioning
confidence: 88%
“…Since the hyperpolarization stabilized at an estimated value close to EK it can be suggested that KATP channels were activated by removal of glucose. To our knowledge this is the first report demonstrating hyperpolarization by glucose deprivation in a cell type other than the pancreatic â_cells (Dean, Matthews & Sakamoto, 1975;Ashcroft, Ashcroft & Harrison, 1988) and the glucose-sensitive neurons (Ashford, Boden & Treherne, 1990). Since hyperpolarization induced by glucose removal was observed in pyruvate-containing as well as pyruvate-free solutions, the ATP generated by pyruvate oxidation in the mitochondria apparently did not affect the activity of KATP channels.…”
Section: Hyperpolarization Induced By Glucose Deprivationmentioning
confidence: 88%
“…For instance, an arrest of the Na/K pump can theoretically be the cause as well as the consequence of decreased metabolism. However, the depolarization of B-cells produced by alloxan is not expected to result from an impaired energy production, since classical uncouplers or inhibitors of glucose metabolism hyperpolarize B-cells [12,28]. A direct effect of alloxan on the Na/K pump is thus plausible [6].…”
Section: Effect Of Alloxan On Rubidium Effluxmentioning
confidence: 99%
“…The latter concept was already proposed as a working hypothesis by several investigators (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%